Syphilis screening among female sex workers in Bangalore, India: comparison of point-of-care testing and traditional serological approaches. Issue 3 (3rd December 2009) - Mishra, Sharmistha; Naik, Balaji; Venugopal, B; Kudur, Prakash; Washington, Reynold; Becker, Marissa; Kenneth, John; Jayanna, Krishnamurthy; Ramesh, Banadakoppa M; Isac, Shajy; Boily, Marie-Claude; Blanchard, James F; et al.
Abstract : Objectives: We undertook a prospective evaluation of the Qualpro Syphicheck-WB rapid syphilis test to measure its diagnostic performance and utility as a point-of-care (POC) screening test among female sex workers (FSWs) in Bangalore, India. Methods: From August 2008 to May 2009, FSWs without a laboratory-confirmed history of syphilis attending STI clinics in Bangalore underwent POC syphilis screening using finger-prick whole blood, with onsite treatment if indicated. Serum samples were collected for local laboratory offsite rapid plasma reagin (RPR) testing and reference laboratory RPR, Treponema pallidum haemagglutination assay (TPHA), and rapid syphilis testing. FSWs who participated in standard offsite RPR screening from August 2007 to May 2008 in the same clinics formed the comparison group for treatment coverage. Results: Of the 1617 women who underwent POC syphilis testing, 7.4% had laboratory evidence of active syphilis with reactive RPR and TPHA, and 3.7% had an RPR titre ≥1:8. Compared with the reference RPR and TPHA, the sensitivity and specificity of the POC syphilis test were 70.8% (95% CI 62.7 to 79.0) and 97.8% (95% CI 97.1 to 98.5). Because of the low rate of women returning for their test results after offsite RPR screening, the proportion of women with active syphilis who were appropriately treated rose from 44.8% to 68.3% with the use of POC syphilis screening (p=0.003). Conclusion: The Syphicheck-WB test utilising finger-prick whole blood has a relatively low sensitivity in detecting active syphilis. However, among hard-to-reach populations who may not return for follow-up treatment, POC screening with this assay could still confer an advantage over offsite RPR testing with respect to treatment coverage.